The Effectiveness of the Microsoft Sway Assisted Discovery Learning Model - Afnyya, Nuni; Setyasto, Novi (Elementary School Teacher, 2021)
This study aims to test the effectiveness of the Discovery Learning model assisted by Microsoft Sway on PPKn learningoutcomes and to describe students in PPKn learning. This type of research is a quasi experimental design withnonequivalent control group design. The population of this study were fourth grade students of Gugus Wahidin, GrabagDistrict and the samples were fourth grade students of SDN Pesidi as the experimental class and fourth grade students ofSDN Ketawang 02 as the control class using cluster random sampling technique. Data collection using tests, observation,and documentation. The learning outcomes test used in the form of a pretest and posttest in the form of multiple choices.The data analysis used was hypothesis testing, gain test, and descriptive analysis. The results showed that the experimentalclass was 77% higher than the control class, namely 64%. The conclusion of this research is that the Discovery Learningmodel assisted by Microsoft Sway which is used in PPKn learning material forms of socio-cultural diversity in Indonesiacan improve learning outcomes. so as to develop student social interactions that include aspects of cooperation,communicative, and solidarity.Keywords: Discovery Learning; Microsoft Sways; PPKn